(untitled) (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
ABSTRACT The article examines the representation of Plato’s allegory of the cave in the film Room, linking philosophy and psychoanalysis to explore liberation, knowledge, and identity formation. Through an interdisciplinary bibliographic review, the author interprets Jack’s transition from confinement to freedom as a metaphor for the movement from shadows to light in Plato’s narrative. The study reflects on the human experience, self-discovery, and the importance of autonomy in the development of the self, emphasizing cinema’s role as a critical and philosophical medium.